2000
DOI: 10.1034/j.1399-3054.2000.1100405.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of glutathione reductase in Brassica juncea: Effects on cadmium accumulation and tolerance

Abstract: showed no chlorosis, and their chlorophyll fluorescence To determine the importance of glutathione reductase (GR, EC 1.6.4.2) for heavy metal accumulation and tolerance, a parameters F v /F m and photochemical quenching were higher. bacterial GR was expressed in Indian mustard (Brassica Cadmium tolerance at the whole-plant level (plant growth) juncea L.), targeted to the cytosol or the plastids. GR activ-was not affected. The lower cadmium stress experienced by the cpGR chloroplasts may be the result of reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 11 publications
(18 reference statements)
1
28
0
Order By: Relevance
“…Likewise, increased γ -glutamylcysteine synthetase activity (encoded by gsh1) occurs in roots and shoots of maize seedlings exposed to Cd (Rüegsegger and Brunold, 1992), and increased glutathione synthetase activity (encoded by gsh2) has been reported in roots of another pea genotype (Rüegsegger et al, 1990). Induction of glutathione reductase (encoded by gr) has been suggested to provide defence against oxidative damage imposed by HM (Dixit et al, 2001), higher tolerance to Cd stress in chloroplasts, and decreased Cd accumulation in shoots (Pilon-Smits et al, 2000). In legumes, synthesis of hGSH has also been implicated in plant responses to HM through the activity of a homoglutathione synthetase encoded by hgsh2, reported as being preferentially expressed in roots and nodules of M. truncatula (Klapheck, 1988;Frendo et al, 1999Frendo et al, , 2001).…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, increased γ -glutamylcysteine synthetase activity (encoded by gsh1) occurs in roots and shoots of maize seedlings exposed to Cd (Rüegsegger and Brunold, 1992), and increased glutathione synthetase activity (encoded by gsh2) has been reported in roots of another pea genotype (Rüegsegger et al, 1990). Induction of glutathione reductase (encoded by gr) has been suggested to provide defence against oxidative damage imposed by HM (Dixit et al, 2001), higher tolerance to Cd stress in chloroplasts, and decreased Cd accumulation in shoots (Pilon-Smits et al, 2000). In legumes, synthesis of hGSH has also been implicated in plant responses to HM through the activity of a homoglutathione synthetase encoded by hgsh2, reported as being preferentially expressed in roots and nodules of M. truncatula (Klapheck, 1988;Frendo et al, 1999Frendo et al, , 2001).…”
Section: Discussionmentioning
confidence: 94%
“…This key enzyme dedicated to re-reduction of glutathione disulfide (GSSG) at the expense of NADPH, contains highly conserved disulfide bridges that may undergo cleavage by heavy metals resulting in inhibition of its activity (Schützendübel et al, 2001). Although Pilon-Smits et al (2000) reported that the chloroplastic GR assumes crucial functions in Cd-tolerance in Brassica juncea, this isoform is probably not involved in our nonphotosynthetic tissues and further work should therefore focus on the cytosolic isoform. It has also been demonstrated that Cd may reduce GR activity despite the fact that it up-regulated the corresponding gene expression (Rodríguez-Serrano et al, 2006) and both transcriptional and post-translational impacts of Cd on this enzyme should therefore be considered.…”
Section: Discussionmentioning
confidence: 97%
“…It has been established that dehydration tolerance requires a coordinated series of events that are associated with preventing oxidative damage and maintaining the native structure of macromolecules and membranes (Hoekstra et al, 2001). Although Cd is not a transition metal able to catalyse the Fenton reaction, numerous authors demonstrated that it may be directly or indirectly responsible for several cellular disorders linked to oxidative stress (Pilon-Smits et al, 2000;Schützendübel et al, 2001;Garnier et al, 2006;Rodríguez-Serrano et al, 2006). It is therefore worth noting that the lipid peroxidation index, estimated on the basis of MDA concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that enhanced chloroplastic GR activity in transgenic plants results in increased protection against oxidative stress (Broadbent et al, 1995;Foyer et al, 1995;Pilon-Smit et al, 2000). In addition, transgenic plants over-expressing superoxide dismutase (SOD) and APX were found to be more tolerant than wild-type plants to a combination of temperature and high light (Allen, 1995;Yabuta et al, 2002).…”
Section: Discussionmentioning
confidence: 99%